Characterization of forming and sintering parameters in producing high quality components through warm compaction - Rahman M.M.; Nor S.S.M.; Rahman H.Y. (2023)
This paper presents the outcomes of an experimental investigation on the effect of forming and sintering parameters to the quality of final products formed at above ambient temperature. The powder mass was prepared by mechanically mixing iron powder ASC 100.29 with 0.3 and 0.6 wt% of zinc stearate for 30 minutes. Solid cylindrical shape green samples were prepared by forming the powder mass at 30C, 150C, and 180C by applying 100 kN axial load simultaneously from top and bottom punches. The defect-free samples were sintered in an argon gas fired sintering furnace by varying the sintering schedule. The as-formed green samples and the sintered products were characterized through density measurement, mechanical testing, and microstructure evaluation. The results revealed that high quality green samples could be produced by mixing 0.6 wt% zinc stearate with the main powder constituent and forming the powder mass at 180C. The high quality finals products were obtained by sintering the green samples at 1000C for 60 minutes at a heating/cooling rate of 10C/minute.